FACTORS FOR THE DEVELOPMENT OF "MUSIC" EDUCATION IN PRIMARY EDUCATION - Jabborova O.M.; Khojamkulov P. (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the effective factors for the development of "Music" in primary education